New bounds from searching for muonium to antimuonium conversion - Willmann, Lorenz; Schmidt, Peter Vaughan; Grossmann, Alex; Jungmann, Klaus; Meyer, Volker; Merkel, Jesko Friedrich; Putlitz, Gisbert zu; Reinhard, Irene; Träger, Konrad (Arxiv, 1998)
A new upper limit for the probability of spontaneous muonium to antimuonium conversion was established at ${\rm P_{M\bar{M}}} ≤ 8.2 · 10^{-11}$ (90%C.L.) in 0.1~T magnetic field, which implies consequences for speculative extensions to the standard model. Coupling parameters in R-parity violating supersymmetry and the mass of a flavour diagonal bileptonic gauge boson can be significantly restricted. A Z$_8$ model with radiative mass generation through heavy lepton seed and the minimal version of 331-GUT models are ruled out.